2004
DOI: 10.1164/rccm.200401-112oc
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Lung Function and Airway Inflammation in Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is defined by progressive, irreversible airflow limitation and an inflammatory response of the lungs, usually to cigarette smoke. However, COPD is a heterogeneous disease in terms of clinical, physiologic, and pathologic presentation. We aimed to evaluate whether airflow limitation, airway responsiveness, and airway inflammation are separate entities underlying the pathophysiology of COPD by using factor analysis. A total of 114 patients (99 males/15 females, age 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 43 publications
4
72
0
Order By: Relevance
“…Similar results have also been shown in patients with chronic obstructive pulmonary disease: in a recent factor analysis, sputum markers, lung function, and IgE/PC 20 comprise nonoverlapping factors. 15 The use of atopic and inflammatory markers as reliable measurements in asthma diagnosis has been supported in a number of studies, [30][31][32] and there is growing evidence that these measures of asthma health status are effective management strategies in improving clinical outcomes. 31,33,34 In our study, peripheral eosinophils, atopic markers, and PC 20 consistently loaded on the same factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have also been shown in patients with chronic obstructive pulmonary disease: in a recent factor analysis, sputum markers, lung function, and IgE/PC 20 comprise nonoverlapping factors. 15 The use of atopic and inflammatory markers as reliable measurements in asthma diagnosis has been supported in a number of studies, [30][31][32] and there is growing evidence that these measures of asthma health status are effective management strategies in improving clinical outcomes. 31,33,34 In our study, peripheral eosinophils, atopic markers, and PC 20 consistently loaded on the same factor.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown evidence that when inflammatory markers (eosinophils and Fractional exhaled nitric oxide [FE NO ]) are included in the factor analysis, they comprise factors distinctly separate from symptoms and lung function. [15][16][17] Although previous studies have used clinical data to identify some of the nonoverlapping dimensions in asthma health status, no one factor analysis has yet combined symptom information, lung function measurements, inflammatory markers, and atopic measures in a large population of children with asthma. The purpose of this study is to provide a comprehensive picture of the heterogeneous factors that make up asthma health status in children by using a large number of variables not previously analyzed together.…”
mentioning
confidence: 99%
“…For example, noninvasive ventilation in patients with hypercapnic respiratory failure, lung volume reduction surgery in patients with upper lobe disease and oxygen for hypoxemic patients have all been shown to reduce mortality. More recently identified phenotypic characteristics include markers of airway inflammation such as exhaled nitric oxide, sputum eosinophils and neutrophils [24,25].…”
Section: Defining Phenotypes In Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…COPD is a multicomponent disease, comprising emphysema in the lung parenchyma, large central airway inflammation and mucociliary dysfunction, bronchiolitis and small airway structural changes [3]. Together, these separate factors contribute to the chronic airflow limitation that characterises the condition [3,4]. In addition, there is evidence that systemic inflammation and extrapulmonary effects are also common in COPD, although the association between systemic inflammation and systemic manifestations of COPD is still not entirely clear.…”
mentioning
confidence: 99%